Cohort Mortality Study in Three Ceramic Factories in Jingdezhen in China - 张小康 王海椒 祝笑敏 刘跃伟 汪利民 戴启瓷 蔡年娥 邬堂春 陈卫红 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
To investigate the health impacts of crystalline silica mixed dust and other potential occupational hazards on workers in ceramic factories, a cohort study of 4851 workers registered in the employment records in 3 ceramic factories in Jingdezhen city of China between 1972 and 1974 was identified. The cohort mortality was traced throughout 2003 with an accumulation of 128970.2 person-years, revealed 1542 deaths. Standardized mortality ratios （SMRs） were calculated for the main causes of death by using Chinese national mortality rates as reference. The mortality from all causes in three ceramic factories was 12.0‰ and the cumulative mortality was 31.8%. Malignant neoplasm, cardiovascular diseases, respiratory diseases, infectious diseases were the first four illnesses that threaten workers’ life, and they accounted for 73.2% of all deaths. The results of this study showed that the standardized mortality ratio for all subjects was 1.02, which is very close to that expected on the basis of the China national mortality rates. Statistically significant mortality excesses for respiratory disease （SMR=1.36）, pneumoconiosis （SMR=37.34）, infectious disease （SMR=5.70） and pul- monary tuberculosis （SMR=3.88） were observed. The mortality of 2938 dust-exposed workers was higher than that of 1913 non dust-exposed workers. Except for pneumoconiosis, the mortality from lung cancer, non-malignant respiratory diseases and pulmonary tuberculosis in dust-exposed workers were significantly increased as compared with that in non-exposed workers, and the relative risks （RRs） were 1.86 （1.16–2.99）, 2.50 （1.84–3.40）, 1.81 （1.34–2.45）. The exposure-response relationships between cumulative dust exposure level and mortality from all causes, colorectal cancer, lung cancer, respiratory diseases, and pulmonary tuberculosis were also identified. The findings indicated that silica mixed dust in ceramic factories has harmful impact on the workers’ health and life span in ceramic factory.